Improving Students’ Motivation In English Vocabulary Mastery Through Mobile Learning - Nur Amalia Solikhah (Wanastra: Jurnal Bahasa dan Sastra, 2020)
The objectives of this research are to improve the students’ motivation through mobile phones as learning (m-learning) media in teaching vocabulary to improve students’ interest to start to give attention with their teacher in English vocabulary learning. The respondents of this research are students of the Information System study program. This Action Reseach is consists of two (2) cycles with five (5) actions in each cycle. In collecting the data, this research used multiple-choice as a test for English vocabulary mastery, observation to obtain data on students’ activities,  field note to record about the general classroom situations, and questionnaires to obtain information from the students in the sense of a report about their English vocabulary learning through mobile learning media. Based on the data analysis of pre-test, post-test 1 in the first cycle, post-test 2 in the second cycle, the mean score is 61.37, 66.06, and 73.42. Then, the data analysis of the observation list in pre-cycle to the first cycle and the second cycle is 42.18%, 49.47%, and 70.97%. It supports the questionnaire data that more than 70% of the students agreed that mobile learning media could motivate them and increasing their English vocabulary mastery. The result of this research showed that Mobile Phone as Learning Media is effective in improving students’ motivation in English vocabulary mastery.